Alley cropping sequentially cropped maize and cowpea with Leucaena on a sandy soil in southern Nigeria - Kang, B.T.; Grimme, H.; Lawson, T.L. (1985)
The potential of alley cropping maize and cowpea with the giant Leucaena (Leucaena leucocephala (Lam) de Wit) cultivar K-28 was studied on an Entisol (Psammentic Ustorthent) in Southern Nigeria. In this trial the crops were grown in 4 m wide alleys formed by periodically pruned leucaena hedgerows. The effect of application of leucaena prunings, nitrogen fertilizer and tillage was studied.